Actin-related protein 2/3 complex subunit 2-enriched extracellular vesicles drive liver cancer metastasis - Mei, Piaorong (2022)
Background: Extracellular vesicles (EVs) play pivotal roles in tumor growth, cancer metastasis and angiogenesis. Here, we aimed to identify proteins that contribute to the functionality of EVs derived from metastatic hepatocellular carcinoma (HCC) cells. Methods: Proteins of EVs derived from metastatic HCC cells and normal liver cells were analyzed by mass spectrometry. Proteomic profiling identified actin-related protein 2/3 complex subunit 2 (ARPC2) to be highly expressed in EVs of metastatic HCC cells. The expression of ARPC2 in EVs and HCC tissues was examined using immunoblotting and TCGA database, respectively. The functional roles of EV-ARPC2 were investigated by knockout approach and various in vitro and in vivo assays. Results: ARPC2 was highly expressed in EVs of metastatic cells but barely detected in non-metastatic HCC cells and normal liver cells. Immunogold labeling showed the presence of APRC2 on the surface of EVs. Analysis of TCGA database of liver cancer revealed ARPC2 overexpression was correlated with poor prognosis of patients. ARPC2 was knockout in metastatic HCC cells. EVs derived from knockout cells displayed compromised activity in enhancing cell growth, motility and metastasis compared to EVs of control cells. Pimozide, an inhibitor of APRC2, also inhibited the promoting effect of EVs of metastatic cells in lung colonization of tumor cells in mice. Conclusion: This study reveals previously unreported expression and function of ARPC2 in EVs. EVs with highly expressed ARPC2 enhance cancer cell growth and metastasis. ARPC2 may provide a prospective target for the novel treatment of HCC patients.